A Description of Personal Health Information Management Work With a Spotlight on the Practices of Older Adults: Qualitative e-Delphi Study With Professional Organizers - Deborah E Seale; Cynthia M LeRouge; Malgorzata Kolotylo-Kulkarni (JMIR Publications, 2023)
BackgroundPersonal health information (PHI) is created on behalf of and by health care consumers to support their care and wellness. Available tools designed to support PHI management (PHIM) remain insufficient. A comprehensive understanding of PHIM work is required, particularly for older adults, to offer more effective PHIM tools and support. ObjectiveThe primary objective of this study was to use the Patient Work System model to provide a holistic description of PHIM work from the perspective of professional organizers with experience assisting health care consumers, including older adults, in managing their PHI. A secondary objective was to examine how factors associated with 4 Patient Work System components (person, tasks, tools and technologies, and context) interact to support or compromise PHIM work performance. MethodsA modified e‐Delphi methodology was used to complete 3 web-based rounds of open-ended questions and obtain consensus among a panel of 16 experts in professional organizing. Data were collected between April and December 2017. The Patient Work System model was used as a coding schema and guided the interpretation of findings during the analysis. ResultsThe PHIM work of adults who sought assistance focused on the tasks of acquiring, organizing, and storing 3 classifications of PHI (medical, financial, and reference) and then processing, reconciling, and storing the medical and financial classifications to tend to their health, health care, and health finances. We also found that the complexities of PHI and PHIM-related work often exceeded the abilities and willingness of those who sought assistance. A total of 6 factors contributed to the complexity of PHIM work. The misalignment of these factors was found to increase the PHIM workload, particularly for older adults. The life changes that often accompanied aging, coupled with obscure and fragmented health care provider- and insurer-generated PHI, created the need for much PHIM work. Acquiring and integrating obscure and fragmented PHI, detecting and reconciling PHI discrepancies, and protecting PHI held by health care consumers were among the most burdensome tasks, especially for older adults. Consequently, personal stakeholders (paid and unpaid) were called upon or voluntarily stepped in to assist with PHIM work. ConclusionsStreamlining and automating 2 of the most common and burdensome PHIM undertakings could drastically reduce health care consumers' PHIM workload: developing and maintaining accurate current and past health summaries and tracking medical bills and insurance claims to reconcile discrepancies. Other improvements that hold promise are the simplification and standardization of commonly used financial and medical PHI; standardization and automation of commonly used PHI acquisition interfaces; and provision of secure, Health Insurance Portability and Accountability Act (HIPAA)-certified PHI tools and technologies that control multiperson access for PHI stored by health care consumers in electronic and paper formats.